Sustained Effectiveness of a Fixed-Dose Combination of Artesunate and Amodiaquine in 480 Patients with Uncomplicated Plasmodium falciparum Malaria in Côte d'Ivoire. (7th December 2017) - Assi, Serge Brice; Nguessan, Abouo Franklin; Aba, Yapo Thomas; Toure, André Offianan; Menan, Hervé; Yavo, Jean Claude; San, Koffi Moïse; Bissagnéné, Emmanuel; Duparc, Stephan; Lameyre, Valérie; Tanoh, Mea Antoine
Abstract : The objective of this study was to monitor the effectiveness of artesunate-amodiaquine fixed-dose combination tablets (ASAQ Winthrop®) in the treatment of uncomplicated Plasmodium falciparum malaria in Côte d'Ivoire. Two enrolment periods (November 2009 to May 2010 and March to October 2013) were compared using an identical design. Subjects with proven monospecific P. falciparum infection according to the WHO diagnostic criteria were eligible. 290 patients during each period received a dose of ASAQ Winthrop tablets appropriate for their age. The primary outcome measure was PCR-corrected adequate clinical and parasitological response at Day 28 in the per protocol population (255 in Period 1 and 240 in Period 2). This was achieved by 95.7% of patients during Period 1 and 96.3% during Period 2. Over 95% of patients were afebrile at Day 3 and complete parasite clearance was achieved at Day 3 in >99% of patients. Nineteen adverse events in nineteen patients were considered as possibly related to treatment, principally vomiting, abnormal liver function tests, and pruritus. There was no evidence for loss of effectiveness over the three-year period in spite of strong drug pressure. This trial was registered in the US Clinical Trials Registry (clinical.trials.gov) under the identifier numberNCT01023399 .